Tuning the reactivity of Sp1 zinc fingers with platinum complexes. Issue 21 (12th May 2016) - Du, Zhifeng; de Paiva, Raphael E. F.; Qu, Yun; Farrell, Nicholas
Abstract : The microenvironment around a zinc finger coordination unit affects the reactivity of apparently similar ZFs with Lewis acid platinum electrophiles. The unique dicysteine-bridged dinuclear platinum unit is the product of the reaction of [PtCl2 (en)] and the F3 of the transcription factor Sp1. Abstract : cis -DDP presents reactivity towards the transcription factor Sp1-F3, as opposed to previous observations for Sp1-F2. Replacing the ammine ligands with the chelating ethylenediamine increases the reactivity giving a unique dinuclear Pt(en)2 -bis(cysteine)-bridged product, confirmed by study of the binding sequence ACPECP.